Synthesis, characterization and solubility studies of four new highly water soluble 1,3,5-triaza-7-phosphaadamantane (PTA) salts and their gold(I) complexes - Schäfer, Sascha; Frey, Wolfgang; Hashmi, A. Stephen K.; Cmrecki, Vesna; Luquin, Asunción; Laguna, Mariano (Polyhedron, 2010)
The synthesis of new water soluble N-alkylated derivatives of 1,3,5-triaza-7-phosphaadamantane is presented. The compounds were characterized by means of NMR and IR spectroscopy, mass spectrometry, high resolution mass spectrometry, elemental analysis and X-ray diffraction analysis. The water solubility of these compounds was found to be up to an astonishing 1450g/L. Several different reactions were performed utilizing these highly interesting compounds as starting materials. It was shown that the substitution of the counter ion can be performed easily. Also transformations at the PTA framework were possible, as shown by an ester cleavage example. To prove that the resulting PTA derivatives are competent as ligands for transition metals, gold(I) complexes were synthesized, using Au(tht)Cl as the metal source. The resulting gold(I) complexes were characterized by 1H NMR and IR spectroscopy, mass and high resolution mass spectrometry or elemental analysis.